Tratamiento endoscópico de lesiones quísticas supratentoriales en pediatría - Grisotto, L; Gómez Avalos , JM; Colombo , G; JL, Bustamante; D´Agustini , MO (Revista Argentina de Neurocirugía, 2020)
Introduction: Neurosurgical endoscopy is a minimally invasive technique, used since the beginning of the 20th century to solve pathologies localized in the ventricular system. Currently the indications for this technique have been greatly expanded. The objective of this work is to present the endoscopic treatment of supratentorial brain cysts of different etiologies in pediatrics. Material and methods: We carried out a retrospective cross-sectional study, from January 2016 to December 2019, of pediatric patients with supratentorial cystic lesions treated endoscopically at the Hospital de Niños of La Plata City. To define success, we used the 5-degree classification of Ross et al. Results: 14 procedures were performed in 12 patients, aged between 2 months and 9 years. Of the total, 6 were intraventricular cysts, 3 midline cysts, 5 paraventricular cysts. All presented any signs or symptoms at the time of the consultation, prevailing among them the alteration of the neurological state and vomiting. After endoscopic fenestration was performed, they presented a favorable clinical evolution in 12 of the 14 procedures and an improvement in at least one imaging criterion in 10 of all procedures. Based on the categorization of Ross et al. we obtained a grade I in 57% of the cases, which implies a permanent complete improvement. The overall complication rate was 7%, presenting post-endoscopy infection in only one case. Conclusion: Neuroendoscopy should be considered as a first-line option for the treatment of supratentorial cystic lesions. It proved to be a non-invasive method, with which we obtained good results and a low complication rate.